Impact of Oil Price Shocks on Sudan's Government Budget - Rahma, Elsiddig; Perera, Noel; Tan, Kian (International Journal of Energy Economics and Policy, 2016)
There is well established literature on the negative relationship between oil price shocks and aggregate macroeconomic activities for developed economies. However, there is a paucity of similar empirical studies in developing countries. In this respect, Sudan is a prominent example. This paper attempts to address this gap by employing the Vector Auto-Regression model to explore the impact of oil price shocks on the main variables of the Sudan government budget using quarterly data for the period 2000:q1-2011:q2. The empirical results suggest that oil price decreases significantly influences oil revenues, current expenditure and budget deficit. However, oil price increases do not Granger cause budget variables. Results from the impulse response functions and forecast error variance decomposition analysis suggest that oil price shocks have asymmetric effect on government budget. Keywords: VAR model, oil price shocks, Sudan JEL Classifications: C320, Q430, O55